A pin-type ultraviolet photodetector based on perovskite-like CsAg2I3 polycrystalline thin film and its preparation method
By using a non-lead-based perovskite CsAg2I3 polycrystalline thin film and pin junction structure of ultraviolet photodetector, the problem of existing silicon-based detectors being insensitive to the UV band is solved, and the effects of self-drive and low dark current are achieved.
Patent Information
- Application Number
- CN202411644823.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-18
- Publication Date
- 2025-03-14
- Estimated Expiration
- 2044-11-18
AI Technical Summary
Existing silicon-based ultraviolet photodetectors have low response sensitivity to the ultraviolet band, and filters are required to reduce interference from visible light and infrared radiation, resulting in complex structure and expensive detectors.
A non-lead-based perovskite CsAg2I3 polycrystalline thin film is used as the light absorption layer, and a hole transport layer and an electron transport layer are prepared on both sides to form a pin junction to form a pin-type ultraviolet photodetector.
It realizes a self-drive mode that can operate without external power supply, has low dark current and good stability, and is suitable for ultraviolet light detection.
Smart Images

Figure CN119153571B_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of new material preparation and photoelectric detector, and specifically relates to a PIN type ultraviolet photoelectric detector with a perovskite-like CsAg2I3 polycrystalline film as a main light-absorbing layer and a preparation method thereof. Background Art
[0002] With the continuous advancement of science and technology, the application of ultraviolet (UV) in many fields such as integrated circuits, space observation, ultraviolet communication, environmental monitoring, water purification, biomedicine, etc. is becoming more and more common. In order to meet the use of ultraviolet in various scenarios, the rapid development of ultraviolet detection technology is crucial. In the past few decades, commercial silicon-based photodetectors have developed rapidly, but due to the relatively narrow band gap width of silicon, the best response of silicon-based detectors to the spectrum is in the visible and near-infrared regions, while the response sensitivity to the ultraviolet band is low. Therefore, it is necessary to install filters to reduce the interference of visible light and infrared radiation on ultraviolet detection, which makes the overall structure of the detector complex and expensive.
[0003] Perovskite has excellent photoelectric properties and adjustable band gap, which makes it have broad prospects in the fields of light-emitting diodes (LEDs), solar cells, detectors, etc. Cesium lead chloride (CsPbCl3) and methylamine lead chloride (CH3NH3PbCl3) have been used for ultraviolet detection, but traditional lead-based perovskites are toxic and have potential hazards to humans and the environment, which does not conform to the green and safe development route. Summary of the invention
[0004] The object of the present invention is to provide a pin-type ultraviolet photodetector based on a perovskite-like CsAg2I3 polycrystalline thin film and a preparation method thereof. The detector uses a non-lead-based perovskite-like material as a light absorption layer, and a hole transport layer and an electron transport layer are prepared on both sides of the light absorption layer to form a pin junction. In order to facilitate electrical connection with an external circuit, electrodes are also prepared on both sides of the hole transport layer and the electron transport layer, respectively, so as to form a complete pin-type ultraviolet photodetector. Specifically, the present invention is implemented by the following technical solutions:
[0005] First, the present invention provides a pin-type ultraviolet photodetector based on a perovskite-like CsAg2I3 polycrystalline film, comprising a GaN substrate, a light absorption layer, and a hole transport layer. The GaN substrate comprises a GaN layer and a sapphire layer (Al2O3), the GaN layer serves as an electron transport layer, the sapphire layer serves as a base layer, and the GaN layer and the hole transport layer are respectively connected with electrodes; the light absorption layer is a non-lead-based perovskite-like material, preferably a cesium silver iodine (CsAg2I3) polycrystalline film is used as the light absorption layer; the GaN electron transport layer is an n-type semiconductor, and matches the energy band structure of the light absorption layer material; the hole transport layer is a cuprous salt, including at least one of cuprous iodide (CuI), cuprous bromide (CuBr), and cuprous thiocyanate (CuSCN), and the hole transport layer thickness is preferably 30 to 100 nm. The hole transport layer is a p-type semiconductor, and matches the energy band structure of the light absorption layer material. The GaN substrate of the present invention can directly adopt a commercial GaN substrate, that is, GaN on a sapphire substrate.
[0006] The electrodes include electrode 1 and electrode 2, wherein electrode 1 is in contact with the hole transport layer, and electrode 2 is in contact with the electron transport layer. The electrodes are not only required to be stable in properties and have good conductivity, but also to form ohmic contact with the contact material. Specifically, electrode 1 is in contact with the hole transport layer, and a material with a high work function, such as gold (Au), nickel (Ni), carbon (C), etc., should be used. Electrode 2 is in contact with the electron transport layer, and a material with a low work function, such as indium (In), gallium (Ga), indium gallium alloy (InGa), etc. should be used.
[0007] Secondly, the present invention also provides a method for preparing the pin-type ultraviolet photodetector based on the perovskite-like CsAg2I3 polycrystalline thin film, which includes the preparation of an electron transport layer or a substrate, the preparation of a light absorption layer, the preparation of a hole transport layer, and the preparation of an electrode.
[0008] Preferably, the preparation of the electron transport layer or substrate includes cleaning the GaN substrate; reserving electrode positions; and hydrophilic treatment.
[0009] Preferably, the preparation of the light absorbing layer comprises the steps of preparing a CsAg2I3 precursor solution, spin coating, and step annealing. The concentration of the CsAg2I3 precursor solution is preferably 0.8-2 mol / L, particularly preferably 0.8-1.2 mol / L.
[0010] Preferably, the hole transport layer is prepared by vacuum evaporation and deposition of cuprous salt using thermal evaporation.
[0011] Preferably, the preparation of the electrode includes depositing a 60-100 nm thick electrode 1 on the hole transport layer by thermal evaporation and preparing an electrode 2 on an electrode reserved area on the GaN substrate by thermal evaporation or scraping.
[0012] Third, the photodetector of the present invention can be used in ultraviolet light detection. The IV characteristics show that the pin-type ultraviolet photodetector based on the perovskite of the present invention has obvious rectification characteristics, indicating that the formation of the pin junction allows the device to work in a self-driven mode. Since the built-in electric field formed by the pin junction reduces the recombination of electrons and holes, the device has a low efficiency of 10 -11 The dark current of level A is very beneficial for weak light detection. At the same time, the detector was tested for 1,500 cycles, and the dark current remained almost unchanged, with the photocurrent only decaying by 3%, reflecting good stability.
[0013] Compared with the prior art, the present invention has the following beneficial effects:
[0014] 1. CsAg2I3 polycrystalline film does not contain lead and is a non-toxic green material;
[0015] 2.CsAg2I3 polycrystalline film has a wide direct band gap (E g = 3.4eV), thus having an intrinsic UV response;
[0016] 3. As an all-inorganic material, CsAg2I3 polycrystalline film has good stability;
[0017] 4. The wide bandgap hole transport layer and electron transport layer match the energy band of the CsAg2I3 polycrystalline film to form a pin junction, allowing the device to work without external power supply. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] Figure 1 This is a device structure diagram of a perovskite-based PIN-type ultraviolet photodetector.
[0019] Figure 2 The energy band diagram of a perovskite-based PIN-type UV photodetector.
[0020] Figure 3 This is an electron microscope photograph of the CsAg2I3 polycrystalline thin film prepared in Example 1.
[0021] Figure 4 This is the IV characteristic curve of the pin-type ultraviolet photodetector prepared in Example 1.
[0022] Figure 5 This is the IT characteristic curve of the pin-type ultraviolet photodetector prepared in Example 1.
[0023] Figure 6 This is the cyclic stability test curve of the PIN type ultraviolet photodetector prepared in Example 1.
[0024] Figure 7This is an electron microscope photograph of the CsAg2I3 polycrystalline thin film prepared in Example 2.
[0025] Figure 8 This is the IV characteristic curve of the pin-type ultraviolet photodetector prepared in Example 2.
[0026] Fig. 9 This is the IT characteristic curve of the pin-type ultraviolet photodetector prepared in Example 2.
[0027] Fig.10 This is the IV characteristic curve of the pin-type ultraviolet photodetector prepared in Example 3.
[0028] Fig.11 This is the IT characteristic curve of the pin-type ultraviolet photodetector prepared in Example 3. DETAILED DESCRIPTION
[0029] The detailed preparation steps of the perovskite-based PIN-type ultraviolet photodetector of the present invention are as follows:
[0030] 1. Preparation of GaN substrate:
[0031] (1) Cleaning: The substrate is ultrasonically cleaned using deionized water, acetone, and anhydrous ethanol in sequence, and then blown dry using nitrogen;
[0032] (2) Electrode position reservation: A reserved position for electrode 2 on one side of the GaN substrate;
[0033] (3) Hydrophilic treatment: Place the substrate in a UV ozone chamber for 10 to 15 minutes to make its surface hydrophilic;
[0034] 2. Preparation of CsAg2I3 polycrystalline thin film:
[0035] (1) Preparation of precursor solution: CsI and AgI were dissolved in DMF at a molar ratio of 1:2, placed on a homogenizer to completely dissolve, and filtered with a 0.22 μm needle filter before use to obtain a clear precursor solution;
[0036] (2) Spin coating: Place the substrate on a spin coater and drop 40-60 μL of CsAg2I3 solution. Spin coating speed: 2000-2500 rpm, duration: 40-60 s.
[0037] (3) Step annealing: After spin coating, transfer the substrate to a hot plate at 50-80°C and anneal for 30 min. Then raise the temperature of the hot plate to 80-110°C and anneal for 30 min.
[0038] 3. Preparation of hole transport layer:
[0039] The hole transport layer was prepared by thermal evaporation. The substrate obtained in the previous step was placed in a vacuum chamber, and the drug (purity>99.999%) was placed on the tungsten boat. The vacuum degree was better than 1×10 -4 Pa, start evaporation, first deposit 5nm at an evaporation rate of 0.1 Å / s, and then deposit 30~100nm at a rate of 0.5~0.8 Å / s.
[0040] 4. Preparation of electrodes:
[0041] (1) Preparation of electrode 1: It is prepared by thermal evaporation. The electrode mask is fixed on the substrate obtained in the previous step and then placed in a vacuum chamber. Electrode metal particles (purity>99.99%) are placed on a tungsten boat. The vacuum degree is better than 1×10 -4 Pa, start evaporation, first deposit 5 nm at an evaporation rate of 0.1 Å / s, and then deposit 60 to 100 nm at a rate of 0.5 to 0.8 Å / s.
[0042] (2) Preparation of electrode 2: In and Ga can be prepared by thermal evaporation, and the specific steps are the same as those for electrode 1. InGa can be heated on a hot plate, dipped with a plastic rod, and evenly scraped on the reserved position on the GaN substrate, taking care not to connect with other parts of the device.
[0043] 5. Device performance test.
[0044] In order to illustrate the performance of the perovskite detector of the present invention, we used a photoelectric detector test system to test the electrical performance of the device, mainly including the following test items:
[0045] (1) IV characteristics: Place the sample on the probe station and apply a scanning voltage to the left and right electrodes to obtain the IV characteristics in the dark state. Then, continuously irradiate the sample with a 365 nm light source to obtain the IV characteristic curve under illumination.
[0046] (2) IT characteristics: Place the sample on the probe station, do not apply bias, and use a 365 nm light source to irradiate the sample at a fixed period to obtain the IT characteristic curve;
[0047] (3) Cycle stability: The circuit connection is the same as the IT characteristic test, the light source frequency is 1 Hz, and the test is repeated for more than 1000 cycles until the waveform is significantly attenuated.
[0048] The present invention is further described below in conjunction with Examples and Comparative Examples, and this description is only for better explanation of the present invention rather than for limiting it. The present invention is not limited to the specific examples and embodiments described herein. Any technician in the art is easy to make further improvements and perfections without departing from the spirit and scope of the present invention, and all fall into protection scope of the present invention. Example 1
[0049] 1. Preparation of GaN substrate: Process the GaN substrate using the above process;
[0050] 2. Preparation of CsAg2I3 polycrystalline thin film: 1 mol / L CsAg2I3 precursor solution was prepared using the above process for preparing CsAg2I3 thin film. 50 μL of CsAg2I3 solution was added during spin coating at a speed of 2500 rpm for 40 s. The step annealing method was annealing at 70°C for 30 min and then annealing at 100°C for 30 min. The prepared CsAg2I3 polycrystalline thin film was characterized using an electron microscope, as shown in FIG. Figure 3 As shown;
[0051] 3. Preparation of hole transport layer: Prepare a 100 nm thick CuI film using the above process;
[0052] 4. Preparation of electrodes: Au is used for electrode 1 and InGa is used for electrode 2. The electrodes are made using the above process;
[0053] 5. Device performance test: The IV characteristics, IT characteristics and cycle stability of the sample were tested using the above test methods, see Figure 4 , 5 、6.
[0054] like Figure 4 As shown, the IV characteristics show obvious rectification characteristics, indicating the formation of a pin junction. Since the built-in electric field formed by the pin junction reduces the recombination of electrons and holes, the device has a low current density of 10 -11 A-level dark current is very beneficial for weak light detection. Figure 5 The demonstrated IT characteristics indicate the good operation performance of the device in self-driving mode. Figure 6 The detector was subjected to 1500 cycles of testing, the dark current remained almost unchanged, and the photocurrent only decayed by 3%, reflecting good stability. Example 2
[0055] 1. Preparation of GaN substrate: same as in Example 1;
[0056] 2. Preparation of CsAg2I3 polycrystalline thin film: A 0.3 mol / L CsAg2I3 precursor solution was prepared using the above process for preparing CsAg2I3 polycrystalline thin film. The spin coating was carried out at a speed of 2000 rpm for 40 s. The other conditions were the same as those in Example 1. The prepared CsAg2I3 thin film was characterized using an electron microscope. Figure 7 As shown;
[0057] 3. Preparation of hole transport layer: same as in Example 1;
[0058] 4. Preparation of electrodes: same as in Example 1;
[0059] 5. Device performance test: Test the IV characteristics and IT characteristics of the sample, such as Figure 8 , Fig. 9 shown.
[0060] like Figure 7 As shown in the figure, the film at 0.3 mol / L is discontinuous and has a large number of voids. This is because there is insufficient solute in the solution, the solvent evaporates quickly during high-speed rotation, a large amount of solute nucleates but there is not enough solute to support the continued growth of the crystal, thus forming a discontinuous film. CsAg2I3 polycrystalline film is used as the middle layer of the pin structure. The discontinuous film will allow the electron transport layer to directly contact the hole transport layer, which will lead to a large leakage current. As shown in the figure, the film at 0.3 mol / L is discontinuous and has a large number of voids. Figure 8 As shown, the dark current is only 10 -10 Level A, which shows that the continuous and dense CsAg2I3 polycrystalline film can effectively reduce the dark current of the device, increase the switching ratio, and thus improve the dark light detection capability of the device. Example 3
[0061] 1. Preparation of GaN substrate: same as in Example 1;
[0062] 2. Preparation of CsAg2I3 polycrystalline thin film: The step annealing method in Example 1 is changed to: annealing at 50°C for 30 min, then annealing at 80°C for 30 min, and the rest is the same as in Example 1;
[0063] 3. Preparation of hole transport layer: same as in Example 1;
[0064] 4. Preparation of electrodes: same as in Example 1;
[0065] 5. Device performance test: Test the IV characteristics and IT characteristics of the sample, such as Fig.10 , Fig.11 shown.
[0066] The present invention uses a non-lead-based perovskite CsAg2I3 polycrystalline film as the main light absorption layer, which has intrinsic ultraviolet absorption and good stability; the wide-bandgap hole transport layer and the electron transport layer match the energy band of the CsAg2I3 polycrystalline film to form a pin junction, and the built-in electric field formed by the pin junction can separate the photogenerated carriers under no bias conditions, so the device can work in a self-driven mode. The present invention has a great promoting effect on the further development of non-lead-based perovskite ultraviolet photodetectors.
[0067] It should be noted that the above embodiments of the present invention are only explanations and clarifications for enabling those skilled in the art to understand the technical essence of the present invention, so the technical contents are not intended to limit the substantial protection scope of the present invention. The substantial protection scope of the present invention shall be subject to the claims. Those skilled in the art should know that any modifications, equivalent substitutions and improvements based on the substantial spirit of the present invention shall be within the substantial protection scope of the present invention.
Claims
1. A pin-type ultraviolet photodetector based on a perovskite-like CsAg2I3 polycrystalline thin film, characterized in that: From bottom to top, it includes a GaN substrate, a light absorption layer, and a hole transport layer. The GaN substrate includes a GaN layer and a sapphire layer. The GaN layer serves as an electron transport layer, and the sapphire layer serves as a base layer. The GaN layer and the hole transport layer are respectively connected with electrodes. The light absorption layer is a non-lead-based perovskite CsAg2I3 polycrystalline thin film. The hole transport layer is a cuprous salt, including at least one of cuprous iodide, cuprous bromide, and cuprous thiocyanate. The electrode includes an electrode one and an electrode two. The electrode one is in contact with the hole transport layer, and the electrode two is in contact with the electron transport layer.
2. The pin-type ultraviolet photodetector based on the perovskite-like CsAg2I3 polycrystalline thin film according to claim 1, characterized in that: The first electrode is made of a high work function metal material, and the second electrode is made of a low work function metal material.
3. The pin-type ultraviolet photodetector based on the perovskite-like CsAg2I3 polycrystalline thin film according to claim 1, characterized in that: The first electrode includes one of gold, nickel, and carbon, or an alloy of two or more thereof, and the second electrode includes one of indium and gallium, or an alloy of two or more thereof.
4. The method for preparing a pin-type ultraviolet photodetector based on a perovskite-like CsAg2I3 polycrystalline thin film according to any one of claims 1 to 3, characterized in that: It includes pretreatment of GaN substrate, preparation of light absorption layer, preparation of hole transport layer and preparation of electrode.
5. The preparation method according to claim 4, characterized in that: The pretreatment of the GaN substrate includes cleaning the GaN substrate, reserving electrode positions, and hydrophilic treatment.
6. The preparation method according to claim 4, characterized in that: The preparation of the light absorption layer includes preparation of CsAg2I3 precursor solution, spin coating, and step annealing.
7. The preparation method according to claim 4, characterized in that: The hole transport layer is prepared by vacuum evaporation and deposition of cuprous salt using a thermal evaporation method.
8. The preparation method according to claim 4, characterized in that: The preparation of the electrode includes depositing a 60-100 nm electrode 1 on the hole transport layer by thermal evaporation and preparing an electrode 2 on the electrode reserved area on the GaN substrate by thermal evaporation or scraping.
9. Application of the pin-type ultraviolet photodetector based on the perovskite-like CsAg2I3 polycrystalline thin film according to any one of claims 1 to 3 in ultraviolet light detection.
Citation Information
Patent Citations
Full-inorganic perovskite nanowire self-energized short-wave photoelectric detector and preparation method thereof
CN111834487A